Mechanistic Interplay between HIV-1 Reverse Transcriptase Enzyme Kinetics and Host SAMHD1 Protein: Viral Myeloid-Cell Tropism and Genomic Mutagenesis - Bowen, Nicole E.; Oo, Adrian; Kim, Baek (Viruses, 2022)
Human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) has been the primary interest among studies on antiviral discovery, viral replication kinetics, drug resistance, and viral evolution. Following infection and entry into target cells, the HIV-1 core disassembles, and the viral RT concomitantly converts the viral RNA into double-stranded proviral DNA, which is integrated into the host genome. The successful completion of the viral life cycle highly depends on the enzymatic DNA polymerase activity of RT. Furthermore, HIV-1 RT has long been known as an error-prone DNA polymerase due to its lack of proofreading exonuclease properties. Indeed, the low fidelity of HIV-1 RT has been considered as one of the key factors in the uniquely high rate of mutagenesis of HIV-1, which leads to efficient viral escape from immune and therapeutic antiviral selective pressures. Interestingly, a series of studies on the replication kinetics of HIV-1 in non-dividing myeloid cells and myeloid specific host restriction factor, SAM domain, and HD domain-containing protein, SAMHD1, suggest that the myeloid cell tropism and high rate of mutagenesis of HIV-1 are mechanistically connected. Here, we review not only HIV-1 RT as a key antiviral target, but also potential evolutionary and mechanistic crosstalk among the unique enzymatic features of HIV-1 RT, the replication kinetics of HIV-1, cell tropism, viral genetic mutation, and host SAMHD1 protein.